Real Time Estimation of the Wind Speed Components Based on Measurement Data from Satellite Navigationand Barometric Measurements - Oleg N. Korsun; Moung Htang Om (RUDN Journal of Engineering Research, 2024)
This research work introduces a robust methodology for estimating three components of wind speed by leveraging airspeed, angle of attack, and sideslip angle measurements from both Satellite Navigation System (SNS) data and on-board sensors. By integrating these diverse sources of information, the proposed algorithm using parametric identification method achieves remarkable accuracy in determining the crucial parameters, i.e. wind speed components, necessary for flight operations. The research was conducted suggesting that the airflow has a constant direction and speed. The estimation of wind speed components is performed for distinct flight duration 20, 31 and 46 seconds in various types of flight maneuver. In order to determine the shortest duration of processing time at which the accurate estimates of three components of wind speed can be ensured, sliding window approach is applied. Notably, this approach yields reliable estimations within an impressive processing time interval of just 0.5 seconds. The findings have significant implications across various domains such as aviation safety enhancement, meteorology applications, and overall operational efficiency improvement of aircraft.